2020
DOI: 10.1155/2020/8037131
|View full text |Cite
|
Sign up to set email alerts
|

Structural Behavior of Concrete Beams Containing Recycled Coarse Aggregates under Flexure

Abstract: The structural behavior of concrete beams containing recycled coarse aggregates (RCAs) was investigated in this study using detailed experimental data. Twelve concrete beams were tested in the experimental program: nine beams with varying RCA contents and three control beams with natural coarse aggregates (NCAs). The parameters for investigating the structural behavior of the RCA concrete beams under flexure were the RCA content (30%, 50%, and 100%) and tensile rebar ratio (0.50%, 0.79%, and 1.14%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Figure 11 shows crack shaping and development in the test samples. Propagation of cracks at different stages was observed by Yang et al [63]. The authors observed a greater number of cracks at the initial cracking stage in the beams with recycled aggregate (RA), compared to the beams with natural aggregate.…”
Section: Resultsmentioning
confidence: 84%
“…Figure 11 shows crack shaping and development in the test samples. Propagation of cracks at different stages was observed by Yang et al [63]. The authors observed a greater number of cracks at the initial cracking stage in the beams with recycled aggregate (RA), compared to the beams with natural aggregate.…”
Section: Resultsmentioning
confidence: 84%
“…The physical properties of the natural coarse and fine aggregates are presented in Table 1. The densities of the natural coarse and fine aggregates were similar at 2.60 and 2.61 g/cm 3 , respectively. The natural fine and coarse aggregates had maximum sizes of 5 and 20 mm, respectively.…”
Section: Methodsmentioning
confidence: 89%
“…CBA was used as a substitute for natural fine aggregates in the mixtures. The test results in Table 1 show that the density of CBA, at 1.84 g/cm 3 , was lower than that of the natural fine aggregate. The water absorption rate of fine CBA aggregate is the rate of the increase in mass due to water in the pores of the fine aggregate.…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations